USAHA PEMAKSIMALAN POTENSI DESA UNTUK MENGURANGI KERUGIAN PETANI MELALUI PRODUK OLAHAN PASTA DAN TEPUNG BAWANG MERAH - Dibihantoro, F.R.; Widyastuti, P.; Sriartini, N.P.P.; Sumardani, N.L.G.; Payani, I.D.A.T.; Wulandari, N.K.P.; Dewi, N.P.S.; Ajidin, A.B.; Hermawan, K.; Maharani, D.A.R.; Widiantari, N.L.P.R.; Novitasari, U.F.; et al. (Buletin Udayana Mengabdi, 2023)
Songan B Village is located in Kintamani District, Bangli Regency, which has the potential for shallot farming which needs to be managed better because the harvested shallots that are sold to the market do not provide added value, especially during the main harvest. The purpose of this community service is to process shallots into flour and shallot paste to reduce the loss of rotting crop residue. The location of Songan B Village, which is near tourist attractions and supported by high demand for shallots, is an advantage in product marketing. Management of shallots into flour and paste is an innovative and creative solution in improving products from shallots. Through this activity, it is hoped that it can empower members of the Songan B Village PKK group to manage shallots as a business opportunity. This service activity is carried out using a combination method between direct activities in the field and online. From the results of the activity, it shows success in increasing the knowledge and skills of the target group as indicated by the increase in the average pretest score of 40.57%, to 86.40%. In addition, the success of this activity was measured from the support of partners who made shallot flour and paste, a creative economic activity characteristic of Songan B Village. Keywords: shallot, flour, pasta, potential, innovation.